Pengaruh Abdominal Stretching Exercise terhadap Penurunan Nyeri Dismenore pada Remaja Putri - Jihan Clearesta Casebella; Rita Riyanti Kusumadewi (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
During menstruation one of the most common complaints experienced by adolescents during menstruation caused by severe contractions of the uterine muscles is called dysmenorrhea. Almost all teenage daughters experience menstrual pain with levels of pain ranging from mild to severe. The absence of teenagers at school is one of the consequences of dysmenorrhea. Abdominal Stretching Exercise is an alternative non-pharmacological therapy option that can reduce dysmenorrhea. During exercise, there will be an increase in the levels of endorphins produced in the brain and also in the spinal cord nerve structure. To find out the impact of abdominal stretching exercises on decreased dysmenorrhea in teenage girls. This type of research is pre-experimental with the design of one group pretest posttest with a sample of 26 respondents. The research tools used in this data collection are the numeric rating scale questionnaire sheet and the observation sheet. The abdominal stretching exercise is performed on the first day of menstruation twice with a duration of 15 minutes. Data analysis using the Wilcoxon test. Before performing abdominal stretching exercises some respondents experienced severe to moderate pain. The Wilcoxon test results showed an Asymp. Sig. (2-tailed) value of <0.05 which means there is an effect of Abdominal Stretching Exercise on Dismenorean Pain Reduction in Teenage Girls. The abdominal stretching exercises have an effect on dismenoreal pain reduction in teenage girls.